The phenomenon of dormant inheritance in inheritance law - O. Ye. Kukhariev (Law and Safety)
The article is devoted to clarifying the essence of the phenomenon of dormant inheritance in inheritance law. It has been concluded that the right of ownership of the inherited property is acquired by the heir retrospectively from the time the inheritance was opened, regardless of the legal regime of the inherited property. However, until the moment of state registration of the right of ownership, the heir is limited in his/her ability to dispose of the inherited real estate, in particular by alienating it. However, this limitation does not at all indicate that the heir has not acquired the right of ownership of the inherited property. The heir can transfer the inherited property to management, enter into an agreement on changing the size of shares in the inheritance.